Measurements of the total neutron cross sections of 93Nb by using the filtered neutron beams. (March 2018) - Anh, Tran Tuan; Son, Pham Ngoc; Tan, Vuong Huu
Highlights: The neutron filter technique has been effectively applied to providing quasi mono-energetic neutron beam lines with qualified characteristics for basic research and related applications at the Dalat research reactor. These neutron beams can be used as mono-energetic neutron sources for measurements of neutron capture and total reaction cross sections. The experimental effective total cross sections at different sample thicknesses of 93 Nb on filtered neutron beams of 24, 54, 133 and 148 keV have been measured based on the neutron transmission method using a proton-recoil neutron spectrometer. The present results with uncertainties within 1.6–6.5% are in good agreement with evaluated data from JENDL-4.0 library and the previous measurements. New updated measurements for total neutron cross sections of 93 Nb in this work are necessary for the EXFOR database. The experimental data obtained in this work are important need for neutron transport simulations, design of fusion reactor, and in evaluation and development of nuclear reaction. Abstract: The total neutron cross sections of 93 Nb in keV energy region were determined by transmission measurements with the filtered neutron beams from the horizontal channel No. 4 of the Dalat research reactor. The natural niobium samples (100% 93 Nb abundance) with a diameter of 20 mm and different thicknesses of 0.0411, 0.0854, 0.1397, 0.2251 and 0.2662 atoms/barn, were prepared from a high purity metallic cylindrical rod. By extrapolating the experimental transmission parameters to the condition of zero thickness, the results of neutron induced total cross sections are 8.50 ± 0.29, 9.13 ± 0.29, 9.79 ± 0.41 and 9.6 ± 0.17 barns, respectively, for the neutron energy beams of 24, 54, 133 and 148 keV. These present results of measurements are compared with the evaluated and literature values.